2019
DOI: 10.1002/bip.23315
|View full text |Cite
|
Sign up to set email alerts
|

Conformation and cooperative order‐disorder transition in aqueous solutions of β‐1,3‐d‐glucan with different degree of branching varied by the Smith degradation

Abstract: β‐1,3‐d‐glucan with different degrees of branching were obtained by selectively and gradually removing side chains from schizophyllan, a water‐soluble triple helical polysaccharide, using the Smith degradation. Size exclusion chromatography combined with a multi‐angle light scattering detection was performed in aqueous 0.1 M NaCl. The degree of branching decreased after the Smith degradation, while the molar mass distributions were almost unchanged. The molecular conformation of the Smith‐degraded β‐1,3‐d‐gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
(94 reference statements)
0
14
0
Order By: Relevance
“…The theoretical T r curves for N = 114 and N = 57 determined from the peak temperatures of theoretical ΔC s curves, as shown in Figure 8A,B, are represented by the dashed curves in Figure 7A. At the lowtemperature side, the DSC data were affected by the tailing, so that the ΔH r data were underestimated especially at low N. 26,27 This underestimation can be estimated with eq 3 by multiplying ΔH r ∞ by f N (280 K), which is the calculated value of f N at 280 K corresponding to the low-temperature limit of the present DSC measurements. The dashed curves in Figure 6A represent the theoretical ΔH r at N = 114 and N = 57 calculated by f N (280 K) × ΔH r ∞ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical T r curves for N = 114 and N = 57 determined from the peak temperatures of theoretical ΔC s curves, as shown in Figure 8A,B, are represented by the dashed curves in Figure 7A. At the lowtemperature side, the DSC data were affected by the tailing, so that the ΔH r data were underestimated especially at low N. 26,27 This underestimation can be estimated with eq 3 by multiplying ΔH r ∞ by f N (280 K), which is the calculated value of f N at 280 K corresponding to the low-temperature limit of the present DSC measurements. The dashed curves in Figure 6A represent the theoretical ΔH r at N = 114 and N = 57 calculated by f N (280 K) × ΔH r ∞ .…”
Section: Resultsmentioning
confidence: 99%
“…A strong molar mass dependency has been observed for the transition temperature ( T r ), while the transition enthalpy (Δ H r ) is unchanged by the sample molar mass, similar to the helix-coil transition of polypeptides. Solvent effects of the transition on T r and Δ H r have been observed by exchanging the solvent from H 2 O to D 2 O, , aqueous NaOH, and H 2 O–dimethyl sulfoxide (DMSO) mixtures. , The CODT behavior of aqueous schizophyllan solutions has been analyzed by linear cooperative transition (LCT) theory, and it was concluded that the transition transforms the ordered structure (triple helix I) constructed between the side chains and water molecules at lower temperature into the disordered structure (triple helix II) at higher temperature. The CODT behaviors for the other analogues of β-1,3- d -glucans with different degrees of branching , and chemically modified schizophyllan derivatives have been investigated. The dependencies on T r and Δ H r were well reproduced in the same manner as schizophyllan by introducing the reduction of the side chains into theory.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the solvent effects, it is needed to control the sample molar mass and the dispersity, because these are sensitive to the CODT behavior. Therefore, we determined T r and Δ H r for sclerox in H 2 O‐DMSO mixtures [ 36 ] and Smith degraded derivative and D 2 O‐DMSO‐d 6 mixtures [ 26 ] from the DSC measurements to investigate the effects of carboxylation and removal of the side chain on CODT in water‐DMSO mixtures.…”
Section: Analysis On Chemically Modified Derivatives In the Mixed Sol...mentioning
confidence: 99%
“…In addition to the solvent effects, it is needed to control the sample molar mass and the dispersity, because these are sensitive to the CODT behavior. Therefore, we determined T r and ΔH r for sclerox in H 2 O-DMSO mixtures [36] and Smith degraded derivative and D 2 O-DMSO-d 6 mixtures [26] from the DSC measurements to investigate the effects of carboxylation and removal of the side chain on CODT in water-DMSO mixtures. Figures 9 and 10 show the composition dependencies of T r and ΔH r for schizophyllan, sclerox in H 2 O-DMSO mixtures, and Smith-degraded derivative in D 2 O-DMSO-d 6 mixtures as a function of x. T r and ΔH r data for schizophyllan were increased with increasing x, reflecting a strong affinity between the side chains and DMSO.…”
Section: Analysis On Chemically Modified Derivatives In the Mixed Sol...mentioning
confidence: 99%
See 1 more Smart Citation